Legal protection for digital consumers: a literature review of the limitations of the civil code in the platform economy era - Muhtadi, Romadh; Fristia Maulana, Ayang (Journal of Law Science, 2025)
The transformation of the global economy towards the digital era has shifted the pattern of consumer and business interaction into the digital platform ecosystem, creating new challenges in consumer legal protection. This study is a systematic, logical, and relevant literature review of the limitations of the Civil Code (KUHPerdata) in responding to the dynamics of digital transactions. This study focuses on how conventional norms in the Civil Code that are oriented towards physical transactions and traditional civil relations have not been able to accommodate the complexity of interactions in a platform-based economy. Through an analysis of the legal theory of consumer protection, the theory of contractual justice, and the progressive legal approach, it was found that the Civil Code is still weak in guaranteeing the principles of transparency, accountability, and protection of personal data in digital transactions. In addition, the legal status of the platform as an intermediary party in the contract between the seller and the buyer creates a vacuum of norms regarding legal responsibility in the event of consumer default or loss. The implications of this finding emphasize the urgency of regulatory reform by adopting adaptive digital consumer protection principles, including updating national legal instruments to align with developments in information technology. This study also recommends the establishment of a new legal framework that specifically regulates consumer protection in the digital ecosystem, to ensure justice and legal certainty amid the rapid growth of the platform economy